ANALISIS PERBEDAAN PENGHINDARAN PAJAK (TAX AVOIDANCE) PADA PERUSAHAAN YANG DIKENAI PAJAK PENGHASILAN FINAL DAN PERUSAHAAN YANG DIKENAI PAJAK PENGHASILAN TIDAK FINAL - Mimi Sartika; Zulbahridar -; Susilatri - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Tax avoidance is an effort by taxpayer to reduce tax expense by not violating the tax laws or other rules in force. However, in fact tax avoidance is something that is not wanted by the government so the government created the rules to prevent it. This study aims to analyze the difference of tax avoidance on companies that deducted final tax and companies that deducted non final tax. Object of study is construction companies, real estate companies, non-construction companies, and non-real estate companies that listed on the Indonesia Stock Exchange period 2009-2013. Determination of the sample is done by using purposive sampling method based on secondary data from financial reports that are available in the Indonesia Stock Exchange Website. The method of analysis used independent sample t-test. The results of this study showed that the companies deducted non final tax tend to do tax avoidance rather than companies that deducted final tax measured by effective tax rate, cash effective tax rate and book tax difference. But, measured by tax planning showed that the companies deducted final tax tend to do tax avoidance rather than companies that deducted non final tax.Keywords: tax avoidance, final tax, non final tax, effective tax rate, cash effective tax rate,book tax difference, and tax planning.